Crecimiento y desarrollo neurocognitivo de niños y adolescentes con infección por VIH en la ciudad de Iquitos, 2025 - Alván Muro, Jessica Samar (2025)
Objective: To determine the relationship between HIV infection and physical growth and neurocognitive development in children and adolescents in the city of Iquitos. Methods: A case–control study was conducted at the Hospital Regional de Loreto and Hospital Apoyo Iquitos, evaluating 21 children and adolescents with HIV and 67 healthy controls from the same age range and locality. Anthropometric measurements and a standardized battery of neurocognitive tests were administered. Caregiver sociodemographic characteristics and antiretroviral therapy (ART) adherence were recorded for associative analysis. Results were obtained through descriptive analysis and inferential statistical tests (Student’s t-test, ANOVA, and correlations analyses) to compare groups and assess associations. Results: The study included 88 participants. Children and adolescents living with HIV presented lower weight and height (p < 0.001), with reduced height-for-age Z scores, interpreted as growth delay. They also showed lower neurocognitive performance in attention (p = 0.02), processing speed (p = 0.01), working memory (p = 0.01), and semantic fluency (p = 0.02). ART adherence was associated with better neurocognitive outcomes (IFS p = 0.009) and higher height-for-age (p < 0.001). Additionally, caregiver educational level, age and type showed a significant relationship with several neurocognitive domains (r = 0.26–0.84). These findings highlight the interaction between clinical and family factors in the physical growth and neurocognitive development of this population. Conclusion: Children and adolescents living with HIV in Iquitos exhibit selective impairments in physical growth and neurocognitive development, influenced by treatment adherence and caregiver educational support.